IMPLEMENTASI KEBIJAKAN PENEGAKAN DISIPLIN PESERTA DIDIK DI SEKOLAH DASAR ISLAM TERPADU AL HIDAYAH - herni hartati; Jeeny Rahmayana (JURNAL ISLAMIKA, 2023)
This study aims to find out, study, explore and describe the Implementation of Policies on Enforcing Student Discipline in Elementary Schools and it is hoped that policies that support success in upholding student discipline can be found. This research was conducted using a qualitative method, research conducted at Al Hidayah Integrated Islamic Elementary School, with the subject of the principal, teachers, educators and students. The research data was collected through observation, interviews and documentation. The results of the research that the authors conducted show that in the process of enforcing student discipline it is carried out through several policies, namely: 1) Policy for enforcing student discipline 2) Establishing rules at school and in the classroom, 3) Monitoring student discipline behavior by making a monitoring book students' daily activities, 4) sanctions for violations, 5) involving school principals, teachers, and parents.